MULAN: FEMALE CHARACTER’S NEGOTIATION TOWARDS PATRIARCHY (EUFONI: Journal of Language, Literary, and Cultural Studies, 2017)
AbstractThis research is aimed at showing the gender inequality in Mulan animated movie (1998). The elements of narrative: setting, plot, and point of view were analyzed through the works of cinematography: angle and shot. The differences between the male and female gender roles were found by examining the dialogues and the song lyrics. The social construction of gender roles was discussed using the ideology of patriarchy by Irigaray (2004) and the concept of Confucianism by Lam (2016). Keywords: Mulan, Gender roles, Cinematography, Patriarchy, Confucianism